The Pass‐Through of a Tax on Sugar‐Sweetened Beverages in Boulder, Colorado. Issue 3 (22nd January 2021) - Cawley, John; Frisvold, David; Jones, David; Lensing, Chelsea
Abstract : This paper estimates the pass‐through of the largest tax on sugar‐sweetened beverages enacted in the U.S., which is two cents per ounce in Boulder, Colorado. A strength of the paper is that, to achieve as complete a perspective as possible, we estimate the pass‐through of the tax not only to beverage prices in retail stores but also to those in restaurants, and we examine data for the treatment community of Boulder and a comparison community of Fort Collins, Colorado, from four sources: ( a ) hand‐collected data on prices from stores; ( b ) Nielsen Retail Scanner Data of store prices; ( c ) hand‐collected data on prices in restaurants; and ( d ) web‐scraped data from online restaurant menus. Across the multiple datasets, we find consistent evidence that the tax was largely, but not completely, passed through to consumers. In both the hand‐collected store data and restaurant data, pass‐through is slightly less than 75%, whereas pass‐through is just over 50% using the scanner data; consumers bear most, but not all, of the largest tax on sugar‐sweetened beverages in the United States.